Some novel exponential function structures to the Cahn-Allen equation - Bulut, Hasan; Atas, Sibel Sehriban; Baskonus, Haci Mehmet (Taylor & Francis as, 2016)
In this manuscript, we consider the Bernoulli sub-equation function method for obtaining new exponential prototype structures to the Cahn-Allen mathematical model. We obtained new results using this technique. We plotted two- and three-dimensional surfaces of the results using Wolfram Mathematica 9. At the end of this manuscript, we submitted a conclusion in a comprehensive manner.
Keywords: Cahn-Allen equation; Bernoulli sub-equation function method; exponential function solution; rational function solution